Tradisi Nyakan Diwang Di Desa Banjar, Kecamatan Banjar, Kabupaten Buleleng (Bentuk, Fungsi, Dan Makna) - Luh Kartika Dewi; Nyoman Suardika; I Putu Ariyasa Darmawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The Nyakan Diwang tradition is a tradition that resides in Banjar Village, Banjar District, Buleleng Regency, where this Nyakan Diwang is a cultural asset for the people of Banjar Village which has been believed to be cleansing from fatigue or dirtiness in sekala and niskala. Nyakan Diwang is a series of Nyepi holidays which fall on pinanggal pisan sasih kadasa, in the background of this research there are problems that can be formulated as follows: (1) What is the form of the implementation of the nyakan diwang tradition in Banjar Village, Banjar District, Buleleng Regency, (2) ) What is the function of carrying out the nyakan diwang tradition in Banjar Village, Banjar District, Buleleng Regency, and (3) What is the meaning of the nyakan diwang tradition in Banjar Village, Banjar District, Buleleng Regency. This study uses theory as a basis for researchers to be able to dissect existing problems, research uses two theories, namely as follows: (1) Structural Functional Theory which will be used to dissect problems in the form of carrying out the nyakan diwang tradition and the function of implementing this nyakan diwang tradition, ( 2) Theory of Meaning used to dissect problems in the meaning of the Nyakan Diwang tradition in Banjar Village, Buleleng Regency. The process of data analysis will produce the following: (1) The form of carrying out the nyakan diwang tradition in Banjar Village includes: a series of carrying out the nyakan diwang tradition, the stages of carrying out the nyakan diwang tradition, and the ending of the nyakan diwang tradition. (2) Functions in carrying out the nyakan diwang tradition, some of the functions used include: social functions where this function has social interactions between people in the nyakan diwang tradition to support the smooth implementation of this tradition, the Thanksgiving function has been carried out in the nyakan diwang tradition, besides that grateful for the belief of the people who believe that the implementation of nyakan diwang is a cleansing of jagadhita (natural harmony).